Management of Diabetic Retinopathy - Ellis, D (The Medical Association Of Malawi, 2013)
Sub-Saharan Africa faces an epidemic of diabetes. Visual loss from diabetic retinopathy (DR) is both preventable and treatable. This article reviews the epidemiology and clinical features of DR and current evidence-based interventions in three areas: primary prevention of retinopathy by optimum medical management, early detection of pre-symptomatic disease and management of established retinopathy to prevent or mitigate visual loss. There are significant challenges to DR care in resource poor environments. Appropriate provision of effective interventions by health services can reduce social and economic costs associated with patient care.